Pengembangan Media Papan Kantong Pintar (PAKAPIN) Untuk Minat Belajar Siswa Kelas IV Dalam Mata Pelajaran Pendidikan Pancasila - Safira, Al Fenia Dewi; Anshory, Ichsan; Danawati, Murtyas Galuh (STKIP Andi Matappa Pangkep, 2024)
The development of PAKAPIN (Smart Pocket Board) media was motivated by problems that occurred at SDN Sisir 03 Batu among class IV students, namely the lack of use of media, too much material content and student learning outcomes that were less than optimal. The aim of the research is to develop PAKAPIN media material